The Impact of Risk Management on the Performance of Deposit Money Banks in Nigeria - Shodeinde, Jide Bolaji (Interdisciplinary Journal Of Lifelong Learning, 2025)
This study investigates the impact of risk management on the performance of deposit money banks in Nigeria. Given the increasingly volatile economic environment, risk management has become a critical focus in the banking sector. Despite the pivotal role banks play in national development, they continue to face a wide range of financial risks. The study specifically aimed to examine the impact of credit risk on the performance of deposit money banks in Nigeria. An ex-post facto research design was employed, with five banks purposively selected for the period 2014–2023. The findings revealed that risk management measured by the loan-to-deposit ratio, liquidity coverage ratio, and liquidity ratio has a significant positive effect on return on assets in the selected banks. The study recommended that Nigerian banks need to strengthen their capabilities in liquidity and credit risk management, as well as loan administration, while regulators should focus more on ensuring banks comply with prudential guidelines.